Coping with mental health issues: subjective experiences of self-help and helpful contextual factors at the start of mental health treatment. (2nd January 2016) - Biringer, Eva; Davidson, Larry; Sundfør, Bengt; Lier, Haldis Ø.; Borg, Marit
Abstract: Background : Self-help strategies and various contextual factors support recovery. However, more in-depth knowledge is needed about how self-help strategies and supportive environments facilitate the recovery process. Aims : To explore what individuals who have recently been referred to a specialist Community Mental Health Center experience as helpful and what they do to help themselves. Method : Ten service users participated in in-depth interviews within a collaborative-reflexive framework. A hermeneutic-phenomenological approach was used. Results : Participants described a variety of helpful strategies and environmental supports. Four relevant main themes were identified: helpful activities, helpful people and places, self-instruction and learning about mental problems and medication and self-medication. Conclusions : The process of recovery is initiated before people become users of mental health services. This study confirms that recovery takes place within the person's daily life context and involves the interplay of contextual factors, such as family, friends, good places, work and other meaningful activities. The coping strategies reported may represent an important focus for attention and clinical intervention.